2013
DOI: 10.3342/kjorl-hns.2013.56.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Treatment Failure in Benign Paroxysmal Positional Vertigo

Abstract: Background and ObjectivesZZParticular repositioning maneuver (PRM) have been recommended as a treatment of benign paroxysmal positional vertigo (BPPV). Some patients require multiple treatments for remission, although most of the patients are treated at the first trial of single maneuver. The purpose of this study was to evaluate risk factors for the treatment failure in patients with posterior canal BPPV (p-BPPV) and horizontal canal BPPV (h-BPPV). Subjects and MethodZZRetrospective review was performed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Kim et al . have reported inner ear disease and hearing loss in the same side as factors related to treatment failure with Epley manuever which is in concordance with our study [ 22 ]. In a similar study Sato et al .…”
Section: Discussionsupporting
confidence: 93%
“…Kim et al . have reported inner ear disease and hearing loss in the same side as factors related to treatment failure with Epley manuever which is in concordance with our study [ 22 ]. In a similar study Sato et al .…”
Section: Discussionsupporting
confidence: 93%
“… 4 , 7) In the previous study by the authors, it was observed that the number of procedures needed to treat p-BPPV (1.7±1.40) was significantly lesser than the number of procedures needed to treat h-BPPV (2.0±1.25), and we can expect that performing the Epley maneuver to treat p-BPPV first would be helpful for achieving quicker recovery when the posterior and horizontal semicircular canals are affected. 15) …”
Section: Discussionmentioning
confidence: 99%
“…The composition of the bifunctional catalysts reported in the literature [11] aims to achieve a balanced synergy of the capacity of the metallic and acid functions (i) a high hydrogenation capacity and (ii) a limited advance of gasification reactions and deactivation due to coke formation. Noble metals (Ru, Rh, Pt, Pd) are active at a relatively low temperature and usually lead to highly hydrogenated end products [12][13][14][15][16]. Zhang et al [17] were able to avoid coke formation over a Ru catalyst by using super/sub-critical ethanol as a solvent for the organic fraction of bio-oil, and obtaining a hydrocarbon yield of 23.2 wt%.…”
Section: Introductionmentioning
confidence: 99%